Development and validation of a quantitative PCR to detect Parvicapsula minibicornis and comparison to histologically ranked infection of juvenile Chinook salmon, Oncorhynchus tshawytscha (Walbaum), from the Klamath River, USA - True, K (Journal of fish diseases, 2009)
Parvicapsula minibicornis is a myxosporean parasite that is associated with disease in Pacific salmon during their freshwater life history phase. This study reports the development of a quantitative (real-time) polymerase chain reaction (QPCR) to detect P. minibicornis DNA. The QPCR assay targets the 18S ribosomal subunit gene. A plasmid DNA control was developed to calibrate cycle threshold (C(T)) score to plasmid molecular equivalent (PME) units, a measure of gene copy number. Assay validation revealed that the QPCR was sensitive and able to detect 50 ag of plasmid DNA, which was equivalent to 12.5 PME. The QPCR assay could detect single P. minibicornis actinospores well above assay sensitivity, indicating a single spore contains at least 100 times the 18S DNA copies required for detection. The QPCR assay was repeatable and highly specific; no detectable amplification was observed using DNA from related myxozoan parasites. The method was validated using kidney tissues from 218 juvenile Chinook salmon sampled during the emigration period of March to July 2005 from the Klamath River. The QPCR assay was compared with histological examination. The QPCR assay detected P. minibicornis infection in 88.1% of the fish sampled, while histological examination detected infection in 71.1% of the fish sampled. Good concordance was found between the methods as 80% of the samples were in agreement. The majority of the disconcordant fish were positive by QPCR, with low levels of P. minibicornis DNA, but negative by histology. The majority of the fish rated histologically as having subclinical or clinical infections had high QPCR levels. The results of this study demonstrate that QPCR is a sensitive quantitative tool for evaluating P. minibicornis infection in fish health monitoring studies